2012
DOI: 10.1063/1.4753811
|View full text |Cite
|
Sign up to set email alerts
|

Wave packet calculations on nonadiabatic effects for the O(3P)+HF(1Σ+) reaction under hyperthermal conditions

Abstract: We present wave packet calculations of total and state-to-state reaction probabilities and integral cross sections for the nonadiabatic dynamics of the O((3)P)+HF → F((2)P)+OH((2)Π) reaction at hyperthermal collision energies ranging from 1.2 to 2.4 eV. The validity of the centrifugal sudden approximation is discussed for the title reaction and a comprehensive investigation of the influence of nonadiabatic effects on the dynamics of this reactive system at high (hyperthermal) collision energies is presented. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…Very recent study on N + H 2 (HD,D 2 ) demonstrated that the cheaper CS approximation has done well for this reactive system. In the wave packet calculations on the nonadiabatic O( 3 P) + HF reaction with direct and rather fast dynamics, the CS approximation showed a good agreement with the CC calculation in computing both the total and the state‐to‐state integral cross sections. The full dimensional quantum dynamics study of tetraatomic D + H 2 O and D + HOD reactions revealed that the CS approximation does not work well for these reactions.…”
Section: Introductionmentioning
confidence: 99%
“…Very recent study on N + H 2 (HD,D 2 ) demonstrated that the cheaper CS approximation has done well for this reactive system. In the wave packet calculations on the nonadiabatic O( 3 P) + HF reaction with direct and rather fast dynamics, the CS approximation showed a good agreement with the CC calculation in computing both the total and the state‐to‐state integral cross sections. The full dimensional quantum dynamics study of tetraatomic D + H 2 O and D + HOD reactions revealed that the CS approximation does not work well for these reactions.…”
Section: Introductionmentioning
confidence: 99%